(untitled) (Boletín Semillero de Investigación en Familia, 2021)
Narrative research in the field of Nursing has become a fundamental tool to identify the subjectivities of health care. Through it, nursing practices can be transformed, facilitating a better understanding of existence, based on the knowledge of the reality felt and interpreted by the people who require care. Throughout the text you will find different citations and experiences that show the importance of guiding future research with a qualitative-narrative approach, which will surely help to humanize health care in the region.